Perancangan E-Modul “ALKI” Pada Mata Pelajaran Kimia Bagi Siswa Kelas X Berbasis Mobile di SMAN 1 Mapat Tunggul - Aisyah Amini; Riri Okra (Department of Science and Technology Ibrahimy University, 2021)
ALKI is an e-module that serves as a learning medium for grade X students majoring in MIA at SMAN 1 MAPAT TUNGGUL. E-module ALKI was created with the aim of assisting teachers in delivering materials and helping students understand more about chemical materials by repeating lessons, working on exercises, and strengthening memory by playing flashcards. The thing behind the design of alki e-module is the lack of motivation to learn students, difficulty and the absence of internet network in Mapat Tunggul area, students should not take home the package book, the smartphone owned by students is not used to study, and when doing homework with the help of the internet most students just copy the answer without understanding the origin of the answer. This research method is Research and Development (R&D) with a 4-D research model (four-D) that is with define, Design, Development, and Disseminate stages. In the Development stage, the development stage of ALKI e-module media is carried out. The media development model used in this study is MDLC(Multimedia Development Life Cycle) luther-sutopo version which consists of 6 stages, namely conception, design, material collection, manufacturing process, testing and distribution. The result of the research is a mobile-based ALKI e-module product. With 0.81 validity test results declared valid,0.93 Practicality test results are practiced very practically,and 0.80 effectiveness test results are declared very effective. So, it can be concluded that alki e-module based on mobile application as a learning medium has been valid, practical and effective.